Natural killer (NK) cell-derived extracellular-vesicle shuttled microRNAs control T cell responses - Sara G Dosil; Sheila Lopez-Cobo; Ana Rodriguez-Galan; Irene Fernandez-Delgado; Marta Ramirez-Huesca; Paula Milan-Rois; Milagros Castellanos; Alvaro Somoza; Manuel José Gómez; Hugh T Reyburn; Mar Vales-Gomez; Francisco Sánchez Madrid; et al. (eLife, 2022)
Natural killer (NK) cells recognize and kill target cells undergoing different types of stress. NK cells are also capable of modulating immune responses. In particular, they regulate T cell functions. Small RNA next-generation sequencing of resting and activated human NK cells and their secreted extracellular vesicles (EVs) led to the identification of a specific repertoire of NK-EV-associated microRNAs and their post-transcriptional modifications signature. Several microRNAs of NK-EVs, namely miR-10b-5p, miR-92a-3p, and miR-155-5p, specifically target molecules involved in Th1 responses. NK-EVs promote the downregulation of GATA3 mRNA in CD4+ T cells and subsequent TBX21 de-repression that leads to Th1 polarization and IFN-γ and IL-2 production. NK-EVs also have an effect on monocyte and moDCs (monocyte-derived dendritic cells) function, driving their activation and increased presentation and costimulatory functions. Nanoparticle-delivered NK-EV microRNAs partially recapitulate NK-EV effects in mice. Our results provide new insights on the immunomodulatory roles of NK-EVs that may help to improve their use as immunotherapeutic tools.